Penegakan Hukum Terhadap Tindak Pidana Illegal Loging Bagi Kelestarian Lingkungan Hidup di Indonesia - Irwan Triadi; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The problem of illegal logging in Indonesia is no longer new. The number of illegal logging cases makes Indonesia one of the countries with the highest number of illegal logging cases in the world. This research aims to understand and examine law enforcement against illegal logging crimes. The method used in this research is the normative juridical method, which is research that aims to find and formulate legal arguments through analysis of the main problem by conducting library research and analyzing primary and secondary legal materials. The analysis is carried out by studying laws and regulations and other literature such as books, journals, and research results related to law enforcement against illegal logging crimes. Violators can be subject to imprisonment, administrative sanctions, and payment of compensation, but often the criminal sanctions imposed do not have a deterrent effect. Therefore, the government must increase supervision in the eradication of illegal logging, especially in vulnerable areas that are often targeted by illegal logging perpetrators.